Ulcerative colitis results in differential metabolism of cranberry polyphenols by the colon microbiome in vitro. Issue 24 (30th November 2021) - Sirven, Maritza Ashton; Venancio, Vinicius Paula; Shankar, Smriti; Klemashevich, Cory; Castellón-Chicas, Maria Joselyn; Fang, Chuo; Mertens-Talcott, Susanne U.; Talcott, Stephen T.
Abstract : Microbiota composition of the colon microbiome influences polyphenol metabolism. Abstract : The microbiome plays a major role in polyphenol metabolism, producing metabolites that are bioavailable and potentially more bioactive than the compounds from which they are derived. However, the microbiome can vary among individuals, and especially for those with co-morbidities, such as ulcerative colitis. In subjects with ulcerative colitis, the consequence of a 'dysbiotic' microbiome is characterized by decreased diversity of microbiota that may impact their capability to metabolize polyphenols into bioavailable metabolites. On this premise, the microbiome metabolism of cranberry polyphenols between healthy individuals and those with ulcerative colitis was compared in vitro . Fecal samples from volunteers, with or without diagnosed ulcerative colitis, were cultured anaerobically in the presence of cranberry polyphenols. The resulting metabolites were then quantified via LC-ESI-MS/MS. 16S rRNA metagenomics analysis was also utilized to assess differences in microbiota composition between healthy and ulcerative colitis microbiomes and the modulatory effects of cranberry polyphenols on microbiota composition. Healthy microbiomes produced higher ( p < 0.05) concentrations of 5-(3′, 4′-dihydroxyphenyl)-gamma-valerolactone and 3-hydroxyphenylacetic acid in comparison to ulcerative colitis microbiomes. Additionally, healthy microbiomes contained a higher ( p < 0.05) abundance of Ruminococcaceae, which could explain their ability to produce higher concentrations of cranberry polyphenol metabolites. Health status and the presence of cranberry polyphenols also significantly impacted the production of several short-chain and branched-chain fatty acids. These results suggest that efficiency of polyphenol metabolism is dependent on microbiota composition and future works should include metabolite data to account for inter-individual differences in polyphenol metabolism.